Relationships during Quarantine: The Justifications for Supporting Psychological Abuse in Women - Paiva, Tamyres Tomaz (2022)
Objective. This online cross-sectional research aimed to analyze the role of attitudes towards conjugal coexistence, during the period of quarantine, as a justification of the relationship between ideologies based on traditionalism and the acceptance of psychological abuse on women. Method. For this purpose, 260 women from different regions of Brazil were studied. Results. The results showed positive and significant effects (mediated effect = .14; SE = .04; 95% CI .05; .22), suggesting that women who endorse more traditionalist ideologies use more justifications, through quarantine, and are more accepting of psychological abuse. This same relationship occurred in the direct and indirect strategies of psychological abuse. Therefore, this study presented preliminary evidence about a possible reinforcer of psychological abuse.